Advanced Textile Based Polymer Composites: Synthesis, Characterization and Applications - Noman, Muhammad Tayyab; Petrů, Michal (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
At present, the textile sector is involved in many diversified fields for the development and sustainability of novel products and polymer-based composites, with several challenges present when it comes to producing innovative, novel, and durable materials. The fabrication of textiles and polymer-based composites as advanced and multifunctional materials in applied industries is a core fundamental concept of this Special Issue, including textile materials, their structures, surface-treated textiles, nanocoated textiles, mathematical modeling, and the use of artificial intelligence (machine learning) for the predicting their most important parameters; textile material reinforcement in composites and polymer composites; and the synthesis, characterization, and applications of textile-based polymer composites for economic and environmental sustainability. This Special Issue covers the following research topics: Synthesis and characterization of functional textiles-natural, synthetic, blended, etc.; Synthesis and characterization of polymer composites-natural, synthetic, hybrid, inorganic, etc.; Analysis of developed composites-interfacial, mechanical, thermal, physical, etc.; Surface treatment of textile-based polymer composites-coating, sorption processes. etc.